Novel structural determinants of single-channel conductance in nicotinic acetylcholine and 5-hydroxytryptamine type-3 receptors. (25th October 2006) - Peters, J.A.; Carland, J.E.; Cooper, M.A.; Livesey, M.R.; Deeb, T.Z.; Hales, T.G.; Lambert, J.J.
Abstract : Nicotinic ACh (acetylcholine) and 5-HT3 (5-hydroxytryptamine type-3) receptors are cation-selective ion channels of the Cys-loop transmitter-gated ion channel superfamily. Numerous lines of evidence indicate that the channel lining domain of such receptors is formed by the α-helical M2 domain (second transmembrane domain) contributed by each of five subunits present within the receptor complex. Specific amino acid residues within the M2 domain have accordingly been demonstrated to influence both single-channel conductance (γ) and ion selectivity. However, it is now clear from work performed on the homomeric 5-HT3A receptor, heteromeric 5-HT3A /5-HT3B receptor and 5-HT3A /5-HT3B receptor subunit chimaeric constructs that an additional major determinant of γ resides within a cytoplasmic domain of the receptor termed the MA-stretch (membrane-associated stretch). The MA-stretch, within the M3–M4 loop, is not traditionally thought to be implicated in ion permeation and selection. Here, we describe how such observations extend to a representative neuronal nicotinic ACh receptor composed of α4 and β2 subunits and, by inference, probably other members of the Cys-loop family. In addition, we will attempt to interpret our results within the context of a recently developed atomic scale model of the nicotinic ACh receptor of Torpedo marmorata (marbled electric ray).